Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 

Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids